Olah Fasad sebagai Upaya untuk Mencapai Kenyamanan Termal pada Omahdawa di Surabaya - Septiani, Kintan Syahla; Dewi, Pancawati (ATRIUM: Jurnal Arsitektur, 2024)
Title: Facade Treatment as an Effort to Achieve Thermal Comfort in Omahdawa Surabaya Indonesia is a country with a high population density. Many large cities in Indonesia are currently experiencing an increasing population, while urban land for housing is becoming increasingly scarce, expensive, and limited. Surabaya is one of Indonesia's major cities with such limited land. This land limitation poses challenges for residents when building their homes, such as small land size and limited orientation. Omahdawa is an example of a Surabaya resident’s dwelling with a land width of only 2.5 meters but a length of up to 25 meters and only one orientation towards the West. This research will discuss how to properly manage the facade of Omahdawa so that residents can still get thermal comfort while inside using Autodesk Ecotect Analysis software simulation. The simulation was carried out by comparing thermal comfort in 3 conditions. The first condition is the Omahdawa design without opening response, the second is the existing design using perforated panel doors and windows, and the third is adding a double skin facade made of glass and perforated panels. The results showed that using perforated doors and windows can improve thermal comfort in the room because air flow can enter. Meanwhile, double-skin facades that use perforated panels were more effective in improving thermal comfort than glass materials.